2022
DOI: 10.1177/0734242x221103936
|View full text |Cite
|
Sign up to set email alerts
|

A full-scale black soldier fly larvae (Hermetia illucens) bioconversion system for domestic biodegradable wastes to resource

Abstract: Domestic biodegradable wastes (DBW) pose a threat to environmental quality and human health. Bioconversion via black soldier fly larvae (BSFL; Hermitia illucens L.) is an expedient way for converting ‘waste to resource’ (insect protein and biofertilizer). Although researches abounded in laboratory-reared experiments and bioconversion mechanisms were pertinent, the void of data from actual and full-scale operation restricts the intensification of BSFL technology and its global adoption. Hence, a full-scale BSFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…MSWM: municipal solid waste management. Boumans et al, 2022); decentralised composting (Ali and Rouse, 2004;Zurbrügg et al, 2004Zurbrügg et al, , 2005Rothenberger et al, 2006); anaerobic digestion to generate gas for cooking as well as a compost product (Gunnerson and Stuckey, 1986;Mueller, 2007;Vögeli et al, 2014); breeding insects such as black soldier flies as a source of protein and fertiliser (Diener et al, 2011;Dortmans et al, 2021;Deng, et al, 2023;ur Rehman et al, 2023); and the production of char as a cooking fuel (Lohri et al, 2016;Zabaleta et al, 2018).…”
Section: Changing Attitudes To the Informal Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…MSWM: municipal solid waste management. Boumans et al, 2022); decentralised composting (Ali and Rouse, 2004;Zurbrügg et al, 2004Zurbrügg et al, , 2005Rothenberger et al, 2006); anaerobic digestion to generate gas for cooking as well as a compost product (Gunnerson and Stuckey, 1986;Mueller, 2007;Vögeli et al, 2014); breeding insects such as black soldier flies as a source of protein and fertiliser (Diener et al, 2011;Dortmans et al, 2021;Deng, et al, 2023;ur Rehman et al, 2023); and the production of char as a cooking fuel (Lohri et al, 2016;Zabaleta et al, 2018).…”
Section: Changing Attitudes To the Informal Sectormentioning
confidence: 99%
“…Organic recycling can be carried out at the household, community or decentralised levels, with considerable advantages over larger, more formal schemes. The many options ( Lenkiewicz and Webster, 2017 ; Lohri et al, 2017 ; Zabaleta et al, 2020 ) include direct use as animal feed ( Scheinberg et al, 2010b ; Boumans et al, 2022 ); decentralised composting ( Ali and Rouse, 2004 ; Zurbrügg et al, 2004 , 2005 ; Rothenberger et al, 2006 ); anaerobic digestion to generate gas for cooking as well as a compost product ( Gunnerson and Stuckey, 1986 ; Mueller, 2007 ; Vögeli et al, 2014 ); breeding insects such as black soldier flies as a source of protein and fertiliser ( Diener et al, 2011 ; Dortmans et al, 2021 ; Deng, et al, 2023 ; ur Rehman et al, 2023 ); and the production of char as a cooking fuel ( Lohri et al, 2016 ; Zabaleta et al, 2018 ).…”
Section: Progress In the Global Southmentioning
confidence: 99%
“…Furthermore, mathematical models coupled with real-time data can significantly improve the management of insect-driven waste composting processes. These models take into account environmental parameters such as relative humidity and ambient temperature, which are crucial for insect growth, organic matter decomposition, and nutrient transformation processes [20][21][22][23]. Through the use and application of such strategies, composting facility management and design can be revolutionized, leading to improved performance, economic viability, and the advancement of sustainable waste management solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In the BSF-assisted waste valorization process, previous studies focused on optimizing the quality of larvae for animal feeding purposes [21], while others focused on substrates parameters only [20]. Nonetheless, it is necessary to unravel crucial environmental parameters in the BSF-assisted composting process.…”
Section: Introductionmentioning
confidence: 99%
“…Gligorescu et al [32] found the best feeding treatment testing the bioconversion efficiency in crates with 20,000 BSFL on 8-10 kg of food waste. Yang-Jie et al [35] planned a 4-year full-scale study with containers filled with 6 kg of urban waste inoculated with 8000 BSFL. The containers were racked in rows and layers to treat 15 ton/day of waste.…”
Section: Introductionmentioning
confidence: 99%